The Leadership Styles Impact, In Learning Organizations, And Organizational Innovation Towards Organizational Performance Over Manufacturing Companies, Indonesia - Jennifer Kristiani Adam; Rhian Indradewa; Tantri Yanuar Rahmat Syah (Journal of Multidisciplinary Academic, 2020)
The vitality of commodity prices and trade wars in international trade due to slowed export-oriented domestic manufacturing industries growth. Leadership is considered as one of the important solutions in improving the key performance of Indonesian manufacturing companies because a good leadership style can be enhance organizational learning and stimulate organizational innovation to improve company performance. In this study, we use quantitative approach with survey method to assess how leadership affect in organizational learning and organizational innovation in shaping of organizational performance. Here, we use a questionnaires and distributed over 320 manufacturing employees in company at several cities throughout Indonesia. Furthermore, the data observations are analyzed by using Structural Equation Modelling (SEM) method. The result shows a leadership style is influenced organizational innovation and organizational learning positively and significantly, then the organizational innovation and organizational learning also positively and significantly influenced organizational performance.